Dentigerous cysts associated with impacted third molars in adults after decompression: a prospective survey of reduction in volume using computerised analysis of cone-beam computed tomographic images. Issue 7 (September 2017) - Lizio, G.; Tomaselli, L.; Landini, L.; Marchetti, C.
Abstract: We prospectively investigated in adults the decompression of dentigerous cysts associated with impacted third molars at high risk of iatrogenic damage during extraction. The computerised calculated volumetric postoperative reductions measured by cone-beam computed tomography at four and eight months were correlated with the duration of treatment, initial volume, and patient's age. We prospectively monitored 14 adult patients with 14 dentigerous cysts that were associated with impacted third molars, for eight months after decompression. The mean (SD) reduction in volume during the first eight months was 71 (14) % (51% after the first four months and 20% after the second four months), with a monthly reduction rate of 9%. Both the total decrease in volume (a) and the monthly rate of reduction (b) were significantly associated (p < 0.01) and linearly correlated with the duration of decompression [r (a) = −0.89, r (b) = −0.61] and initial volume [r (a) = r (b) = 0.92], but not with the patient's age (p = 0.49) [r (a) = r (b) = 0.04]. The trend towards reduction in volume within a period of eight months of treatment allowed us to better understand the duration of decompression required.